GAMBARAN PENGETAHUAN REMAJA MENGENAI BAHAYA ALKOHOL DENGAN STROKE - Khosuma, Edward; Kembuan, Mieke; Karema, Winifred (Universitas Sam Ratulangi, 2013)
Abstract.Stroke or brain circulatory disorders as a major problem in the field of neurology. Not only the number of events is increasing, but also that interfere kemungkinasekuel for a long time, and decreased morbidity and increased mortality. During this time, most people just assume that strokes only happen to people in adulthood or old. In fact, stroke can also occur in teenagers. This study aims to describe the level of knowledge of adolescents about the dangers of alcohol and stroke. This is a descriptive study using survey method.The sample were 81 adolescents aged 15-19 years, whose enrolling study at Kristen 1 Senior High School and Manado Internasional School.Datas were collected by questionnaire and short interview. There are 81% of samples at Sonder Christian Senior High School and 80% of samples atManado International Schoolknew the definition of alchohol. 88% of samples at Sonder Christian 1 Senior High School also 80% of samples at Manado International Schoolknew the definition of stroke.59% of sampelsat Sonder Christian Senior High Schooland 61% of samples at Manado International School knew alchohol was one of the cause in stroke incident.Conclusion: More than 50% of sampelsat both schoolscategorized in the group of people who knew the danger of alchohol in relation with stroke. Keywords: Adolelescents, knowledge, alchohol, strokeÂ Abstrak.Stroke atau gangguan peredaran darah otak merupakan problem utama dibidang neurologi. Bukan hanya angka kejadiannya yang makin meningkat, tapi juga kemungkinan tersisanya sekuel yang menggangu untuk waktu yang lama, serta menurunnya morbiditas serta meningkatnya mortalitas. Selama ini, kebanyakan orang hanya menganggap bahwa stroke hanya dialami oleh mereka pada usia dewasa atau tua. Padahal, stroke juga bias terjadi pada remaja. Penelitian ini bertujuan untuk mengetahui gambaran tingkat pengetahuan remaja mengenai bahaya alkohol dengan stroke. Penelitian ini bersifat deskriptif dengan metode survei.Sampel adalah 81 remaja berusia 15-19 tahun yang bersekolah di SMA Kristen 1 Sonderdan SMA MIS. Data didapatkan lewat kuesioner dan wawancara singkat. Sebanyak 81% siswaSMA Kr 1 Sonder dan 80% siswa SMA MIS Manado menjawab ya mereka tahu alkohol itu apa. 88% SMA Kr 1 Sonder dan 80% SMA MIS Manado menjawab mereka sudah tahu tentang stroke, dan 59% SMA Kr 1 Sonder serta 61% SMA MIS Manado sudah mengetahui bahwa alkohol merupakan salah satu penyebab stroke.Simpulan: lebih dari50% responden dikedua sekolah paling banyak dikategori ya mereka tahu mengenai bahaya alkohol dengan stroke. Kata kunci: Remaja, pengetahuan, alkohol, stroke